Trend in the Molecular Characterization and Geographic Distribution of Mycobacterium tuberculosis Complex Strains: A Systematic Review - Bohara, Madan Singh; Bhatta, Dwij Raj (Far Western Review, 2025)
This systematic review aims to evaluate the global molecular characterization of Mycobacterium tuberculosis complex (MTBC) isolates from 2017 to June 2023, focusing on lineage distribution, drug resistance trends, and diagnostic methods. Following PRISMA guidelines, data from 10 high quality studies comprising 7,848 clinical samples across 10 countries were analyzed, yielding 3,216 confirmed MTBC isolates. Spoligotyping, MIRU-VNTR, and whole genome sequencing (WGS) were used to characterize strains, alongside various drug susceptibility testing (DST) methods. Lineage 4 (Euro-American) was the most widespread globally, especially in sub-Saharan Africa and Europe. Lineage 2 (Beijing), associated with multidrug resistance, predominated in South Asia, while Lineage 3 (CAS/Delhi) was prevalent in Pakistan and Sudan. MDR-TB rates varied widely from 1.9% in Ghana to 75% in Ireland with high rates also in Nepal (56.8%) and India (50.6%). Male patients accounted for 64% of MTBC cases, indicating gender disparities in disease burden. Spoligotyping was the most frequently used molecular method, though WGS is increasingly employed for its higher resolution. DST methods included the proportion method on Lowenstein–Jensen medium, MGIT 960, GeneXpert MTB/RIF, and Line Probe Assays (LPA). Findings reveal significant regional variation in MTBC lineages and resistance rates. To improve TB control, there is an urgent need for standardized molecular diagnostics, enhanced regional surveillance, and gender-sensitive treatment strategies. Investment in diagnostic infrastructure, particularly in high-burden regions, is critical to curbing the global spread of MDR-TB.